International students, beneficiaries of the state scholarships of the Republic of Serbia and their education in the 21st century - Vasojević, Nena A. (Sociološki pregled, 2022)
Nowadays, there is an increasing number of international students interested in studying in Serbia. More precisely, ever since the World in Serbia project was first launched in 2010, the number of international beneficiaries of scholarships has been a continuous increase but so far, no research of this population has been done. Results from the past, as well as the launching of the World in Serbia study programme, have inspired us to choose temporary migration of international beneficiaries of student scholarships in Serbia in the 21st century as the subject of our research. The purpose of this paper is to define the profile of international beneficiaries of student scholarships, whose education is funded by the Government of the Republic of Serbia funds, but also to establish motivation that led these students to their decision to study in Serbia. For this reason, we have conducted the research on the basis of a survey, on a sample of 126 international beneficiaries of student scholarships.